The Analysis of Economic Growth, Unemployment Rate and Inflation on Poverty Levels in Indonesia (Using the Vector Error Correction Model (VECM) Method) - Muhammad Faisal; Ichsan Ichsan (Journal of Malikussaleh Public Economics, 2020)
This study aims to determine the effect of economic growth, unemployment, and inflation on the poverty rate in Indonesia. This study uses secondary data taken from 1998 to 2018 accessed on www.bps.go.id. The data analysis method used is the Vector Error Correction Model (VECM) method. The results show that economic growth has no significant effect on the poverty rate, the unemployment rate positively and significantly influences the poverty rate, and inflation has a positive and significant effect on the poverty rate in the short-term. In the long-term, inflation does not significantly influence the poverty rate. Then using the Granger Causality test show that economic growth and poverty have no reciprocal relationship, and ployment and poverty do not have a reciprocal relationship, but only have a one-way relationship, while inflation and poverty have a reciprocal or two-way relationship. It is expected that the Government of Indonesia will be able to find effective solutions to solve the problem of poverty in Indonesia. Keywords: Economic growth, unemployment rate, inflation, poverty level, VECM.